2020
DOI: 10.1163/15685306-bja10029
|View full text |Cite
|
Sign up to set email alerts
|

Human-Animal Studies: Remembering the Past, Celebrating the Present, Troubling the Future

Abstract: This is the third in a series of reports on the state of the field of Human-Animal Studies. In the introductory section, major terms in the prevailing definition of the field—Human-Animal Studies is the interdisciplinary study of human-animal relationships—are unpacked and critically analyzed. Subsequent sections deal with the field’s past, present, and possible futures. A schematic history of the field considers both scholarly contributions and programmatic inroads in the academy. The current state of the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 42 publications
0
10
0
3
Order By: Relevance
“…For example, one specific pathway that humans may benefit from non-conventional companion animals is through their unique care requirements, which require regular and specific effort to maintain. Stronger adherence to routines necessary for exotic companion animal care may recreate the therapeutic effects of behavioral activation through activity scheduling, for which substantial evidence of its applications in treating depression exist [85,86]. This possibility is yet to be explored in research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one specific pathway that humans may benefit from non-conventional companion animals is through their unique care requirements, which require regular and specific effort to maintain. Stronger adherence to routines necessary for exotic companion animal care may recreate the therapeutic effects of behavioral activation through activity scheduling, for which substantial evidence of its applications in treating depression exist [85,86]. This possibility is yet to be explored in research.…”
Section: Discussionmentioning
confidence: 99%
“…Culture-independent comparison studies have revealed that even though the distal portion of the intestinal ecosystem of humans and mice inhabits similar phyla of bacteria, many species and genera of bacteria present in mice are not found in humans. Therefore, when generalizing the findings of the animal studies to humans, caution should be taken [ 237 , 238 ]. Studies carried out in animals to evaluate the impacts of phytochemicals on the alteration in the composition of the gut microbiome are summarized in Table 1 .…”
Section: Mechanism Of Action Of Phytochemicalmentioning
confidence: 99%
“…Human-animal studies have focused on the discontinuity of both humans and non-human animals in society, where discourse has shifted to concentrate on animals as mutually beneficial components for both human and non-human societies (16-21). Contemporary human-animal studies are most broadly understood as the examination of interactions among human and non-human animals, emphasizing the expression of non-human agency (22)(23)(24). In her seminal book, "Animals in Society: An Introduction to Human-Animal Studies," DeMello (25) considers the conceptual construct of non-human animals within the Euro-American cultural context and the ways it reinforces and perpetuates hierarchical human relationships.…”
Section: Literature Review Changing Human Perceptions Of Non-human Animalsmentioning
confidence: 99%